The Normal and Pathological Fetal Brain Ultrasonographic Features - Bault, Jean-Philippe; Loeuillet, Laurence (Springer International Publishing : Imprint: Springer, 2015)
This book provides assistance in preparing for and conducting screening or diagnostic ultrasound examinations of the fetal brain in all stages of pregnancy. Readers are provided with: abundantly illustrated descriptions of studies conducted on normal brain structures using all conventional and 3D/4D ultrasound techniques; a detailed description of the main structures of the brain; photographs of fetal pathology specimens that may be used to compare the results of imaging techniques with the anatomical reality; and practical advice and technical tips. The second part of this book presents a clear and informative overview of fetal brain pathologies, combining a wealth of detailed images and precise descriptions.